Influence of the lipoic acid on the regenerative potential of thiol compounds in the retina in modeling age maculodystrophy in animals with allergic uveitis - Savko , V. V.; Vashah Zijad Mahmud Ahmed (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Urgency of the study consists in investigating the effect of lipoate in treatment of patients with age maculodystrophy. Purpose of the study. To investigate the influence of the lipoic acid on the regenerative potential of thiol compounds in the retina in modeling age maculodystrophy in animals with allergic uveitis. Material and methods. Experimental studies were made in 31 rabbit, which have been divided into 4groups: 1 (control) — 7animals, 2 (with influence of light) — 8 animals, 3 (with influence of light and allergic uveitis) — 8 animals, 4 (with influence of light, allergic uveitis and application of lipoate) — 8 animals. Determination of the restored and oxidized glutathione, as well as thiol and disulfide groups of proteins was made in the tissues of the isolated retina. Results. In modeling AMD the concentration of restored glutathione increases by 38.6 %, and its oxidized form decreases by 29.8 % under the influence of lipoate in conditions of allergic uveitis. The level of the thiol groups of the retinal proteins becomes normalized after the application of the lipoic acid. The level of the thiol groups of proteins and disulfide bonds in these conditions distinctly came nearer to the indices of the norm.